Proces brachycefalizacji na terenie ziem Polski w okresie feudalnym - Kozak, Jerzy (Polskie Towarzystwo Antropologiczne, 1995)
THE PROCESS OF BRACHYCEPHALIZATION IN POLAND IN THE FEUDAL PERIOD. The influence of the urbanisation and the accompanied changes of the social structure upon the process of brachycephaly in Poland was investigated. The sample consisted of 65 skeletal populations (about 5500 individuals from the feudal period 9th -19th century).
THE PROCESS OF BRACHYCEPHALIZATION IN POLAND IN THE FEUDAL PERIOD